Ni and Cu-catalyzed one pot synthesis of unsymmetrical 1, 3-di(hetero)aryl-1H-indazoles from hydrazine, o-chloro (hetero)benzophenones, and (hetero)aryl bromides. Issue 23 (1st June 2017) - Wiethan, Carson; Lavoie, Christopher M.; Borzenko, Andrey; Clark, Jillian S. K.; Bonacorso, Helio G.; Stradiotto, Mark
Abstract : A new nickel-catalyzed cyclization of ortho -chlorobenzophenone hydrazones, to afford 3-aryl-1 H -indazoles, is applied in a one-pot synthesis of 1, 3-diaryl-1 H -indazoles. Abstract : The nickel-catalyzed cyclization of in situ generated ortho -chlorobenzophenone hydrazone derivatives, to afford 3-(hetero)aryl-1 H -indazoles, is documented for the first time. The product 1 H -indazoles can be transformed subsequently in a one-pot procedure into 1, 3-di(hetero)aryl-1 H -indazoles via copper-catalyzed N -arylation with (hetero)aryl bromides.